배우 음성 훈련을 위한 EVT 구조연습 활용방안 - 이영수(Young-Su Lee) (한국콘텐츠학회 논문지, 21(9), 2021)
본 연구는 음성을 예술적 표현 수단의 매개체로 사용하는 배우의 연기 예술에서 음성 기관의 독립적인 조절, 제어를 가능하게 하는 에스틸 보이스 트레이닝(Estill Voice Training) 모델의 이론적 원리와 구조연습 훈련이 배우 음성 운용에 적용될 수 있는 긍정적 효용성을 탐구하는 데 그 목적이 있다. 생성기관의 원리에 기인하여 음성 산출물의 상이점을 조절하는 음성 과학적 방법론에 대한 연구는 심리와 신체를 함께 아우르는 기존의 배우 음성 훈련에 비해 국내에서 활발히 소개되지 못하고 있는 현실이다. 음성은 해부 생리학을 근간으로 우리 몸에 대한 이해가 선행될 때 운용의 정확성과 안정성을 담보할 수 있을 뿐만 아니라 더 나아가 인물 창조의 요소인 인물의 음성적 성격화에도 기여할 수 있다. 배우 음성 훈련에서 자기 수용적 감각을 통한 훈련 모델을 고찰하는 것은 배우가 일련의 목표음을 산출하는 과정에서 원리적이며 실질적인 방법론으로 모색될 수 있다는 실용적 가치와 대안적 의의를 지닌다. In this study, the theoretical principle and structural practice of Estill Voice Training model that enables independent control of voice organs in the actor's acting art using voice as a medium of artistic expression. Its purpose is to explore the positive utility that can be applied to operation. The research on the speech science methodology that controls the differences in speech output due to the principle of the generation organ is a reality that has not been actively introduced in Korea compared to the existing actor's speech training that encompasses both the mind and the body. Voice can guarantee the accuracy and stability of operation when an understanding of our body is preceded based on anatomical physiology as well as contribute to the characterization of the character's phonetic character an element of character creation. Considering the training model through proprioception in actor voice training has practical value and alternative significance that the actor can be sought as a principle and practical methodology in the process of generating a series of target sounds. KCI Citation Count: 0